Changes in anthropometric and metabolic parameters related to gastroesophageal reflux disease in non obese cases - Şeyma Yavuz; Özlem Gül Utku; Aşkın Güngüneş; Nermin Dindar Badem; Bilal Ergül; Dilek Oğuz (Intercontinental Journal of Internal Medicine, 2026)
Aims: Central obesity associated with visceral adiposity is considered to increase reflux symptoms. This study aimed to investigate the effects of anthropometric and visceral fat-related measurements on reflux symptoms in non-obese patients with gastroesophageal reflux disease (GERD) and a body mass index (BMI)